2012
DOI: 10.1525/abt.2012.74.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning About Natural Selection: Diagnosing Contextual Competency Using the ACORNS Instrument

Abstract: Studies of students' thinking about natural selection have revealed that the scenarios in which students reason evoke different types, magnitudes, and arrangements of knowledge elements and misconceptions. Diagnostic tests are needed that probe students' thinking across a representative array of evolutionary contexts. The ACORNS is a diagnostic test that treats different evolutionary contexts as unique scenarios worthy of focused assessment and targeted instruction. Our investigations revealed that ACORNS scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 16 publications
3
113
1
4
Order By: Relevance
“…For our sample of biology students, the reliability of CINS scores (measured with Cronbach's alpha) was 0.7. The second instrument that we used was the newly developed open-response ACORNS (Assessing COntextual Reasoning about Natural Selection; Nehm et al 2012). We used four isomorphic ACORNS items, standardized by familiarity: (1) How would biologists explain how a living mouse species without claws evolved from an ancestral mouse species that had claws?…”
Section: Methodsmentioning
confidence: 99%
“…For our sample of biology students, the reliability of CINS scores (measured with Cronbach's alpha) was 0.7. The second instrument that we used was the newly developed open-response ACORNS (Assessing COntextual Reasoning about Natural Selection; Nehm et al 2012). We used four isomorphic ACORNS items, standardized by familiarity: (1) How would biologists explain how a living mouse species without claws evolved from an ancestral mouse species that had claws?…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of student responses to natural selection items found that students gave different responses depending on the context of the item (Nehm and Ha 2011;Nehm et al 2012;Nettle 2010;Opfer et al 2012;White and Yamamoto 2011). For example, undergraduate biology students said that organisms lost traits over time because they did not use them or that the organism shifted energy allocation to other more important processes, but did not use those ideas to respond to items about trait gain (Nehm and Ha 2011).…”
Section: The Relevance Of Item Context To Student Ideasmentioning
confidence: 99%
“…Related studies have revealed unexpected trends in student responses that would not be captured by answers to multiplechoice questions. For example, students often combine incorrect and correct ideas and answer questions differently depending on their surface features [e.g., a question using bacteria vs. an animal (Nehm et al 2012)]. We will be analyzing student responses to versions of the GCA questions discussed here by assessing the frequency with which students use these persistently incorrect ideas and evaluating their explanations to help us further explore why students have these misunderstandings.…”
Section: Genetics Instructors Can Help Students By Handling Misconcepmentioning
confidence: 99%